High potential of small-room acoustic modeling with 3D time-domain finite element method - Okuzono, Takeshi; Yoshida, Takumi (Frontiers in Built Environment, 2022)
Applicability of wave-based acoustics simulation methods in the time domain has increased markedly for performing room-acoustics simulation. They can incorporate sound absorber effects appropriately with a local-reaction frequency-dependent impedance boundary condition and an extended-reaction model. However, their accuracy, efficiency and practicality against a standard frequency-domain solver in 3D room acoustics simulation are still not known well. This paper describes a performance examination of a recently developed time-domain FEM (TD-FEM) for small-room acoustics simulation. This report first describes the significantly higher efficiency of TD-FEM against a frequency-domain FEM (FD-FEM) via acoustics simulation in a small cubic room and a small meeting room, including two porous-type sound absorbers and a resonant-type sound absorber. Those sound absorbers are modeled with local-reaction frequency-dependent impedance boundary conditions and an extended-reaction model. Then, the practicality of time-domain FEM is demonstrated further by simulating the room impulse response of the meeting room under various sound absorber configurations, including the frequency component up to 6 kHz. Results demonstrated the high potential and computational benefit of time-domain FEM as a 3D small room acoustics prediction tool.